Penguatan Motivasi Berqurban kepada Wali Murid di TKIT Ibunda Jatipuro - Juhdi Amin; Fathurrohman Husen; Rohmatun Nurjanah (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Qurban is the slaughter of livestock to get closer to Allah Almighty on Eid al-Adha on the 10th of Dhul-Hijjah and the days of Tasyriq (11th, 12th, 13th of Dhul-Hijjah). The majority of Indonesia's population is Muslim. A Muslim needs to spend some money to buy sacrificial animals. The problems raised in this service activity were related to the implementation of socialization to strengthen sacrificial motivation to TKIT parents, Mrs. Jatipuro. This activity aims to provide motivation and to find out the parents' understanding of the Sharia and the law of sacrifice. The service method used is Participatory Action Research (PAR), by conducting socialization activities regarding the motivation for sacrifice to the parents of TKIT Ibu students. This activity is carried out through three stages, namely (1) the preparation stage, (2) the implementation stage, and (3) the evaluation stage. The purpose of this devotion is to invite parents to perform sacrifices. This activity is quite important to do because it is to provide an understanding of the fiqh of sacrifice to parents of students. The results of this activity show an increase in understanding of the material conveyed by the servant to the student's guardian. Suggestions for this activity hopefully can be carried out in the following years to provide an understanding of sacrifice to parents of students and so that parents want to make sacrifices at school.